2012
DOI: 10.1007/s10669-012-9420-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical properties of soils in relation to forest composition in moist temperate valley slopes of Garhwal Himalaya, India

Abstract: The present study was undertaken in moist temperate forest of Mandal-Chopta area in the Garhwal region of Uttarakhand, India. The aim of the present study was to assess the chemical properties of soils in relation to the forest structure and composition. Twelve forest types according to the altitude, slope aspect, and species composition were selected for the study. Chemical properties of the soil, i.e., total nitrogen (N), available phosphorus (P), available potassium (K), organic carbon (C), soil organic mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 25 publications
17
36
0
Order By: Relevance
“…Several authors have reported that soil K content is influenced by elevation, total nitrogen, and organic matter (Basumatary & Bordoloi 1992, Gairola et al 2012. In the present study, no significant differences among sites and no significant correlations between K and soil chemical properties were detected, according to previous findings by Paudel & Sah (2003).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several authors have reported that soil K content is influenced by elevation, total nitrogen, and organic matter (Basumatary & Bordoloi 1992, Gairola et al 2012. In the present study, no significant differences among sites and no significant correlations between K and soil chemical properties were detected, according to previous findings by Paudel & Sah (2003).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, the results indicated that the organic matter, the most important nitrogen source (Gairola et al 2012), was higher in Tarkin than in the other sites. Moreover, we observed a significant correlation between total nitrogen and the organic matter, according to Gairola et al (2012).…”
Section: Discussionmentioning
confidence: 85%
“…The values are also similar to the studies done in other parts of Uttarakhand consisting banj oak and pine forests viz. Gairola et al (2012) and Joshi and Negi (2015). Principal component analysis was done to find out the key information from the multivariate dataset by plotting all the data along with first two principal components ( Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…As per Champion and Seth (1968) it is one of the dominant tree species in the tropical moist as well as dry deciduous forests in India. Some previous studies about physico-chemical characterization of soil were also done by researchers in various forests of Kumaun and Garhwal Himalaya (Joshi and Negi, 2015;Khera et al, 2001;Singh et al, 2009;Semwal et al, 2009;Sharma et al, 2010;Jina et al, 2011;Gairola et al, 2012;Kumar et al, 2013;Joshi, et al, 2013;Mehta et al, 2014;Upreti et al, 2016;Tewari et al, 2016;Bharti, et al, 2016). Present study is focused on the comparison of soil physico-chemical profiling of three different forest types (Oak, Pine and Sal) of Betalghat region of Kumaun Himalaya, Uttarakhand.…”
Section: Introductionmentioning
confidence: 99%